Genectic analysis of heading time trait in wheat - Federizzi, Luiz C.; Carvalho, Fernando I. F. de; Nodari, Rubens O. (Pesquisa Agropecuaria Brasileira, 2014)
The inheritance of heading time, in the field, was studied in crosses involving four Brazilian wheats (Triticum aestivum L.) (IAS 55, Nobre, B 20 and PF 70553) and two alien wheats (Yugoslávia 715/70 and NS 1406). The parents, their F1 and F2 cross generations, and the two first backcrosses (BC1F1 and BC2F1) were investigated to obtain a better understanding of how heading time is inherited and to assess the possibility of changing this trait through selection. Gene action appeared to be additive and of dominance. Evidence for epistasis, as an important contributor to heading time, was lacking. A minimum of three genetic factors of blocks of genes appear to control head time. While long cycle wheats carry recessive alleles at all three loci, the short cycles are governed by one two dominant genes. Heritability for heading time was estimated to be high, indicating that considerable progress could be made in shifting mean heading time by selecting and recombining early-heading F2 plants.